Analisis Laporan Keuangan Segmentasi Pada Perusahaan PT Kino Indonesia Tbk - Icha Nurfadhilla; Windi Julianti; Yustin Giftiani; Siti Rodiah (Sekolah Tinggi Ilmu Ekonomi Trianandra, 2023)
Companies going public usually make disclosures on the reporting of segmentation of their company's operations. Segmentation reporting aims for stakeholders to see the company's financial statements behind the consolidated amount for each component that makes up the entity. In PT Kino Indonesia Tbk there are five segments in it, including body care, beverages, food, pharmaceuticals and pet food. This study aims to analyze the segment in accordance with the ten percent test of revenue, profit and loss and assets in the 2018-2022 Annual Report. In analyzing this segment report in accordance with PSAK number 5. The method carried out in this study is a qualitative descriptive method. The results of research at PT Kino Indonesia Tbk, it can be concluded that from these three tests, the average segment that can be reported is the segment (body care, beverages, and food) because it passed the ten percent test. While in the segment (pharmaceutical and pet food) All three tests could not be reported because they did not pass the 10% test. Thus, PT Kino Indonesia Tbk and subsidiaries from 2018 to 2022 are still less effective in implementing PSAK 5.